An Analysis of Teachers' Pedagogical Competence in the Implementation of Thematic Learning at the Elementary School Level - Moch. Fauzi; Riska Amelia Ade Putri; Fifi Fitriana Sari; Ija Srirahmawati (Jurnal Evaluasi dan Kajian Strategis Pendidikan Dasar, 2026)
This study aims to analyze teachers’ pedagogical competence in the implementation of thematic learning in Grade V of SD Negeri 03 Kempo, Dompu Regency. The study employed a descriptive qualitative approach involving one fifth-grade teacher as the main informant and several fifth-grade students as supporting informants. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model consisting of data reduction, data display, and conclusion drawing, with data validity strengthened through source and technique triangulation. The findings indicate that the teacher’s pedagogical competence was reflected in the planning, implementation, and evaluation of thematic learning, particularly in the preparation of instructional documents, the implementation of learning activities based on the assigned theme, and the use of exercises and question-and-answer activities for evaluation. However, cross-subject integration in thematic learning was not yet fully optimized, the teaching methods remained predominantly teacher-centered, and students’ active participation was still limited. The study also identified key constraints, namely limited instructional time and difficulties in designing truly integrative thematic learning activities. These findings underline the need to strengthen teachers’ pedagogical competence so that thematic learning in elementary schools can be implemented in a more integrative, participatory, and meaningful way for students.